STRUCTURAL IMPROVEMENT OF THE WHEEL DRIVE OF A MILITARY VEHICLE - Petrov, L. M.; Kishianus, I. V.; Petryk, Yu. M.; Nikishyn, V. A.; Sheluhin, S. V. (Systems and Technologies, 2023)
The movement of the car is carried out due to the loading of the wheel driver by forces: gravitational force and tangential force of traction, which sometimes leads to a delay in the movement of the rotation of the tire during its deformation, as well as to the incomplete realization of the power created by the engine and which is transmitted to the wheel driver. The article examines the questions and presents elements of the theory of a military vehicle with a structural improvement of the wheel drive of a military vehicle, as well as theorems on the change in kinetic energy of such a wheel drive. The technological diagram of the developed and improved design of the wheel drive allows the process of transferring the motion of the car to be carried out at the expense of the kinematically connected with it movable additional wheel, the transformation of the energy supplied to the wheel drive into the controlled relative to the center of its hub and with the addition of the traction force of the car with the transfer force, which is an auxiliary factor to the innovative technology of its movement. The scientific and practical direction of the work consists in the fact that for the first time the technology is considered in which the law of change of mechanical energy is applied during the rotation of the wheel drive on the road by using the wheel drive with an additional wheel kinematically connected to it. The research methodology was to establish a mathematical relationship between the speed of the cyclic movement of the additional wheel, which is associated with the center of the car wheel hub, and this allows to increase the dynamic mobility of the car directly. The result of the study is the development of elements of the theory of a military vehicle with a new design of a wheel drive with an additional wheel kinematically connected to it, which allows to increase the dynamic mobility of the vehicle directly. The value of the conducted research, the results of the conducted work will allow to make a contribution to the automotive industry. The proposed model of a car with a new design of a wheel drive with an additional wheel kinematically associated with it is suitable for use in order to effectively implement engine power and convert it into traction force on the wheel.